Effect of thermoultrasonic treatment on the antioxidant activity of elderberry (Sambucus nigra L.) juice - L. Ch. Burak; A. P. Zavaley; V. V. Yablonskaya; A. N. Sapach (Пищевые системы)
Numerous studies of the chemical composition of black elderberries have shown that they contain biologically active compounds with high antioxidant capacity. The purpose of the work is to study the effect of thermoultrasonic treatment on the content of biologically active substances and antioxidant activity of elderberry (Sambucus nigra L.) juice. The research objects were freshly squeezed elderberry juice, pasteurized elderberry juice, and juice subjected to thermoultrasonic treatment. The color was determined by the calorimetric method, the total content of flavonoids, anthocyanins and antioxidant activity by DPPH radical scavenging activity of the juice samples were determined using a spectrophotometric method. Thermal treatment with ultrasound was carried out in an ultrasonic homogenizer. It has been found that elderberry juice treated with thermoultrasound had a higher color index (CD), juice brightness values (L*), overall color difference (ΔE) and lower values of hue angle (h), yellow index (YI). The total content of phenols, flavonoids and anthocyanins in the sample treated with thermoultrasound with a power of 600 W, frequency of 20 kHz, and a temperature of 65 °С for 15 minutes was higher by 13.32%, 251.72% and 94.12%, respectively, compared to the untreated sample and sample pasteurized at 65 °С for 30 minutes. The 1,1-diphenyl‑2-picrylhydrazyl (DPPH) and hydroxyl radical (·OH) scavenging activities were increased to 65.22% and 51.13%, respectively, which was significantly higher than those of the control sample. The content of the main anthocyanins cyanidin‑3-O‑sambubioside, cyanidin‑3-O‑glucoside and cyanidin‑3-O‑sambubioside‑5-O‑glucoside was 987.5 mg/dm3, 752.4 mg/dm3 and 191.4 mg/dm3. Correlation analysis has shown that the antioxidant content has a significant effect on the color index of elderberry juice, and cyanidin‑3-O‑glucoside and cyanidin‑3-O‑sambubiositol determine the brightness or darkness of the juice. Heat treatment with ultrasound significantly improves the content of total phenolic compounds, flavonoids and anthocyanins, and helps to increase the antioxidant activity of elderberry juice. The results suggest that this method can be an effective method for pasteurizing elderberry juice while maintaining the quality and antioxidant activity.